PERAN KEBIJAKAN MODERASI BERAGAMA DI PERGURUAN TINGGI ISLAM DALAM MENANGKAL RADIKALISME - Abdul Rasyid; Titi Kadi (STKIP Subang, 2026)
This study analyzes the implementation of religious moderation policies within Islamic Religious Higher Education Institutions (PTKI) as a strategic strategy to counter radicalism. The main issue raised is the vulnerability of students to the infiltration of extreme ideologies that threaten national integration. The significance of this study lies in the need to evaluate national policies such as the 2020-2024 and 2025-2029 National Medium-Term Development Plans (RPJMN) in an academic context. Using a qualitative methodology through a systematic literature review of 20 primary sources and statistical data from various PTKIs, this study found that the establishment of the House of Religious Moderation (RMB) and the integration of the wasathiyah curriculum have significantly increased the student tolerance index, despite still facing challenges such as internal resistance, budget constraints, and digital disruption. The results indicate that religious moderation is effective as an ideological